Serum Lipid Profile, Serum Magnesium and Fasting Serum Glucose in Newly Diagnosed Type 2 Diabetic Subjects (Bangladesh Journal of Medical Biochemistry, 2014)
Type 2 diabetes is considered as a major health burden due to its rising prevalence and disabling, life threatening complications. Dyslipidemia, often coexisting with T2DM as a feature of insulin resistance, is hypothesized to be linked with altered magnesium homeostasis. This study was designed to evaluate the serum magnesium levels and its influence on serum lipids in type 2 diabetics. Lipid profile, serum magnesium (Mg) and fasting serum glucose (FSG) were measured in 30 newly diagnosed normotensive type 2 diabetic patients chosen as cases (Group II) just before introducing any treatment, and was compared with that of 30 healthy controls (Group I). The serum magnesium was found to be significantly lower (p